1980
DOI: 10.1079/bjn19800071
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional evaluation of the germ meal and its protein isolate obtained from the carob seed (Ceratonia siliqua) in the rat

Abstract: I . Evaluation of the germ meal (CGM) of carob seed (Ceratonia siliqua) and its protein isolate was carried out with weanling rats. Comparisons were made with casein, soya-bean meal, whole defatted egg and a soya-bean protein isolate (Promine-D) as protein sources. The growth-promoting effects and certain biological indices were evaluated using the protein efficiency ratio (PER), biological value (BV) and net protein utilization (NPU) bioassay procedures.2. The unsupplemented CGM had a PER of 1-66*0.09 and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…The PER value of the protein isolates varied within the range of 1.61 to 1.69 and the BV value in the range of 0.48 to 0.53. The results revealed that although these values were lower than those obtained for casein, they are in agreement with the values obtained for some standard ebible vegetable proteins such as groundnut protein (PER, 1.7 and BV, 0.54), maize protein (PER, 1.2 and BV, 0.59), soybean protein (PER, 1.6 and BV, 0.49) and sesame protein (PER, 1.7 and BV, 0.60) [20,21].…”
Section: Nutritional Performances Of the Protein Isolatessupporting
confidence: 70%
“…The PER value of the protein isolates varied within the range of 1.61 to 1.69 and the BV value in the range of 0.48 to 0.53. The results revealed that although these values were lower than those obtained for casein, they are in agreement with the values obtained for some standard ebible vegetable proteins such as groundnut protein (PER, 1.7 and BV, 0.54), maize protein (PER, 1.2 and BV, 0.59), soybean protein (PER, 1.6 and BV, 0.49) and sesame protein (PER, 1.7 and BV, 0.60) [20,21].…”
Section: Nutritional Performances Of the Protein Isolatessupporting
confidence: 70%
“…The substrate for EVE production is a mixture of organic wastes co‐product from the dry‐mill bioethanol process (DDGS Distiller's Dried Grain with solubles) coming from wheat and corn grains, a commodity currently used as a nutritional supplement for dairy and beef cattle, and carob germ (the embryos of the seeds), a by‐product processed for animal feedstuffs 30…”
Section: Resultsmentioning
confidence: 99%
“…Obtaining process The substrate for EVE production is a mixture of organic wastes co-product from the dry-mill bioethanol process (DDGS Distiller's Dried Grain with solubles) coming from wheat and corn grains, a commodity currently used as a nutritional supplement for dairy and beef cattle, and carob germ (the embryos of the seeds), a by-product processed for animal feedstuffs. 30 These residues have been modified using an enzymatic attack process to extract protein by reducing the protein size and lead to solubilisation of the original vegetal substrate protein. The enzymatic hydrolysis was carried out using an endoprotease mixture (trypsin-and chymotrypsin-like) as the hydrolytic agent in a bioreactor with the following hydrolysis parameters: substrate concentration 10% w/w in water, with 0.15% CaCl 2 as stabiliser for the enzyme, controlled temperature (60 • C) and pH = 8, using the pH-stat method.…”
Section: Results and Discussion Enzymatic Extractmentioning
confidence: 99%